SISTEM INFORMASI MANAJEMEN PERSEDIAAN BARANG BERBASIS MULTIUSER - Heri Wibowo; Rayyan Firdaus (PT. Intelek Cendikiawan Nusantara, 2024)
At a time when the rapid development of technology and information systems encourages society, both groups and individuals, both government and private agencies, to take advantage of technological developments, technology has a very important role in the progress of human life. Technological developments, one of which is the superiority of computers in processing data, can increase effectiveness, productivity and efficiency in carrying out work. Today's technology makes inventory management easier. Sumber Jaya Building Shop is located at Jl. Ahmad Yani, Dalu Village, Lubuk Pakam District, Deli Serdang Regency, the current inventory and sales system still uses archival paper records. The inventory or procurement process of goods can be done manually, by directly checking the remaining goods. Checking item data and stock data is recorded on a piece of paper by the admin section as a report to the management.